Kuat Tekan Dan Kuat Lentur Beton Geopolimer Abu Terbang Hybrid Dengan Pecampuran Portland Composite Cement - Noviandri, Rizky; Olivia, Monita; Sitompul, Iskandar Romey (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The use of Portland Composite Cement (PCC) as a substitute material in fly ash geopolymer hybrid concrete will accelerate the geopolymer reaction since the geopolymer becomes more reactive. In this study, the fly ash geopolymer hybrid concrete used 12 M NaOH concentration, modulus of silicate (Ms) 2.5 and 15% PCC cement, and extra water 80 kg/m3. Geopolymer hybrid concrete treatment were carried out at room temperature. Tests carried out were compressive strength and flexural strength at 7 and 28 days. The results showed the compressive strength of geopolymer hybrid concrete against PCC concrete had a decreasing percentage of difference from 34,54% (6,68 MPa) at 7 days to 20,01% (4,49 MPa) at 28 days. Then, the percentage of flexural strength difference decreased from 31.09% (1.25 MPa) at seven days to 28.55% (1.39 MPa) at 28 days. It was concluded that fly ash did not significantly affect the split tensile strength of geopolymer hybrid concrete 28 at days.The results showed that the compressive strength and flexural strength of the geopolymer hybrid concrete were lower than these of PCC concrete.Keywords : Mechanical properties, hybrid geopolymer concrete, PCC, room temperature.